The cunning of gender violence : geopolitics and feminism - Abu-Lughod, Lila; Hammami, Rema; Shalhūb-Kīfūrkiyān, Nādirah (Next wave (Duke University Press), 2023)
"The Cunning of Gender Violence focuses on the selective ways a visionary feminist project has folded itself into world affairs. Over the course of two decades, gender-based violence against women has emerged as highly publicized and powerful agenda within international governance and law, increasingly folded into state sovereignty and global security. The volume tracks operations across four circuits of power: global security regimes, states and state violence; the humanitarian-development nexus; and mass media. Through close ethnographic studies and analysis of discourses, the essays explore the ways gender-based violence against women may be affirming, enabling, or sustaining rationales and systems of power and civilizational hierarches that are harmful for many. Through case studies on Palestine, Bangladesh, Iran, India, Pakistan, Israel, and Turkey, as well as U.S. foreign policy and the international legal institutions from the International Criminal Court to the UN Security Council, Cunning of Gender Violence traces the silences and omissions of the governmentalized categories of gender-based violence against women while analyzing its real-world impacts"--